1999
DOI: 10.1063/1.478920
|View full text |Cite
|
Sign up to set email alerts
|

Rotation-tunneling spectrum of the deuterated ammonia dimer

Abstract: Articles you may be interested inThe rotational spectrum and dynamical structure of LiOH and LiOD: A combined laboratory and ab initio study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…The potential surface of ammonia dimer is configurationally complex. In addition to possessing a rather flat intermolecular surface, inversion at nitrogen plays a role in the spectroscopy that is used to determine the experimental structure . The classic microwave study by Nelson, Fraser, and Klemperer, wherein ammonia dimer is found to have an asymmetric structure, is inconsistent with ab initio reports from the 1980s.…”
Section: Discussionmentioning
confidence: 99%
“…The potential surface of ammonia dimer is configurationally complex. In addition to possessing a rather flat intermolecular surface, inversion at nitrogen plays a role in the spectroscopy that is used to determine the experimental structure . The classic microwave study by Nelson, Fraser, and Klemperer, wherein ammonia dimer is found to have an asymmetric structure, is inconsistent with ab initio reports from the 1980s.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies showed the need for further refinement. Karyakin et al 16 determined the A + A states interchange splitting of (ND 3 ) 2 . Their observed value of 264 GHz is about 25% smaller than the calculated 331 GHz, while the calculated A + A interchange splitting of (NH 3 ) 2 of 475 GHz matches the experimental value of 483 GHz very well.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Heineking et al 14 analyzed the 14 N nuclear hyperfine structure of some rotation-inversion transitions in the lowest K ) 1 E 3 state. Behrens et al 15 studied the infrared molecular beam depletion spectrum of the ammonia dimer in cold helium clusters, in which they found that the dominating interchange tunnelings in free ammonia dimers are largely quenched in a superfluid helium cluster at 0.4 K. Finally, Karyakin et al 16 measured the millimeter and submillimeter-wave molecular beam spectrum of the A + A state of (ND 3 ) 2 . Mu ¨ller-Dethlefs and Hobza 17 used the ammonia dimer as an illustrative example in their review article on noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…24,35 The electric field dependent rotational energy level shifts are related to the permanent electric dipole moments (EDMs) of InA via the Stark Hamiltonian, which was added as a perturbation to the asymmetric rigid rotor Hamiltonian in the analysis of the Stark spectra. 24,45 A simulation of the Stark spectrum recorded at an applied electric field of 423 V cm À1 was fit by least squares using 48…”
Section: Fluorescence Excitation Spectramentioning
confidence: 99%
“…This (NH 3 ) 2 arrangement is similar in structure to that found in the (NH 3 ) 2 dimer, as measured in great detail using far-infrared and microwave spectroscopy. [46][47][48] Examples of the optimized structures of InA and InA 2 are shown in Fig. 4.…”
Section: Theoretical Structures and Vibrational Frequenciesmentioning
confidence: 99%